E-Governance Initiatives for Educational Administration and Management - Dr Pavan Kumar Gupta (International journal of economic perspectives, 2022)
“E-Governance is the public sector’s use of information and communication technologies with the aim of improving information and service delivery, encouraging citizen participation in the decision-making process and making government more accountable, transparent and effective. E-Governance involves new styles of leadership, new ways of debating and deciding policy and investment, new ways of accessing education, new ways of listening to citizens and new ways of organizing and delivering information and services”. It is the application of Information and Communication Technology (ICT) for strengthening administration and management in higher education system in India. It has improve the education quality in the past three decades due to tremendous increase in the number of colleges and universities and their privatization. The effective use of IT services in educational Sector can greatly enhance efficiency of the existing system, decrease the costs, and increase transparency in the functioning of various departments. E-governance process brings transparency in the system, so E-governance initiatives in the field of higher education can reduce the malpractice up to a large extent. This type of initiative can give a better interface and opportunity to students, parents, teachers and administrative management. Recently, the University Grants Commission (UGC) has recommended four models of Public Private Partnership to the Planning Commission and according to an estimate, the country requires an investment of over US 150 billion in the next 10 years.